Meningkatkan Kesadaran Sejarah Lokal Melalui Efektivitas Program Museum R.A.A Adwidjaja Goes To School - Puspitasari, Ratih; Astri Indriyani; Heni; M. Devin Putra (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The decline in awareness of local history among the younger generation, especially elementary school students, is a concern in Garut Regency. As an effort to increase understanding and appreciation of local history and culture, the Museum R.A.A Adwidjaja Garut Goes to School program was implemented. This program is a collaboration between the R.A.A Adwidjaja Museum, the Garut Regency Tourism and Culture Office, and KKN students, implemented at SDN 2 Cinunuk and SDN 2 & 3 Wanaraja. This research aims to make the literacy program effective by increasing local history awareness in elementary school students by bringing the R.A.A Adwidjaja Museum to the school environment, so that students can get closer to local history material through museum collections such as heirlooms, historical photographs, and ancient manuscripts. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation of program activities. The results showed that the program succeeded in increasing students' interest and knowledge of Garut local history, especially through the interactive approach applied in educational activities. However, some factors such as limited time and space in schools become challenges that need to be overcome for the sustainability of this program in the future. The results of this study are expected to contribute to the development of a more effective local history education program, as well as a reference for other institutions that want to implement a similar program. In addition, this program is expected to be sustainable and have a long-term impact on historical awareness among the younger generation in Garut Regency.